Prevalence and risk factors of low bone mineral density in patients with multiple sclerosis. Issue 3 (June 2015) - Coskun Benlidayi, I.; Basaran, S.; Evlice, A.; Erdem, M.; Demirkiran, M.
Abstract : Objectives: To determine the prevalence and risk factors of low bone mineral density (BMD) in patients with multiple sclerosis (MS). Methods: Patients with MS who had undergone a BMD evaluation via dual-energy X-ray absorptiometry (DXA) between January 2010 and December 2013 were included in the study. Descriptive data, BMD values, and risk factors for osteoporosis along with the details regarding MS, such as age at onset, duration of disease, clinical type of MS, expanded disability status scale (EDSS) scores, and lifetime steroid intake were obtained from the medical record database and telephone interview. Results: The study group comprised 67 patients with a mean age of 41·1 ± 10·2 years. Of the patients, 20·9% revealed low BMD for chronological age. Vitamin D insufficiency (25(OH)D < 20 ng/ml) rate was 86·6%. Comorbidity and EDSS scores of patients with low BMD were significantly higher than those of the remaining patients ( P = 0·000 and P = 0·015, respectively). Neck BMD was inversely correlated with comorbidity score, disease duration, relapse number, and lifetime steroid intake ( r = − 0·270, r = − 0·263, r = − 0·359, and r = − 0·314, respectively). Conclusion: The current study revealed that low BMD and vitamin D insufficiency were common in patients with MS. Longer disease duration, higher comorbidity score, and severe disability level led to lower BMD values. In conclusion, it is of paramount importance for clinicians to pay more attention on bone health in MS and to tailor preventative measures meticulously.